Fatalism in breast cancer and performing mammography on women with or without a family history of breast cancer - Maryam Molaei-Zardanjani; Mitra Savabi-Esfahani; Fariba Taleghani (BMC, 2019)
Abstract Background Breast cancer is the most prevalent cancer in women, and in those with a positive family history, it is important to perform mammography. One of the probable barriers in doing mammography is fatalism. Methods This is a descriptive/cross-sectional study conducted on 400 women residing in Isfahan, Iran, randomly selected in 2017. Sampling was done randomly among the enrolled women in Health Integrity System. The data collection tool was a questionnaire regarding the demographic-fertility information and fatalism. The data analysis was done by SPSS software. A P-value < 0.05 was considered statistically significant. Results The results showed that the mean rate of fatalism was 59.5 ± 23.2 in women with the experience of mammography, and 65.9±18.7 in women without the experience. Moreover, the mean rate of fatalism was 73.1±15.2 in subjects with a family history of breast cancer, and 59.3 ± 22.5 in those no family history related to this condition. Accordingly, fatalism was statistically significant associated (P < 0.001) with a family history of breast cancer and experience of mammography. There was no significant relationship between demographic information and fatalism (P > 0.05). Conclusion The results indicated that fatalism in women with no experience of mammography was higher than in those with a positive history. Regarding the necessity of mammography in women with a family history of breast cancer, the required interventions seem to be essential to changing the viewpoints of women regarding the importance and effect of mammography as a screening method for breast cancer.